2012
DOI: 10.1038/labinvest.2012.100
|View full text |Cite
|
Sign up to set email alerts
|

MDR1-P-glycoprotein behaves as an oncofetal protein that promotes cell survival in gastric cancer cells

Abstract: P-glycoprotein (P-gp), traditionally linked to cancer poor prognosis and multidrug resistance, is undetectable in normal gastric mucosa and overexpressed in gastric cancer (GC). We propose that P-gp may be involved in Helicobacter pylori (Hp)-related gastric carcinogenesis by inhibiting apoptosis. Aim of the study was to evaluate the expression of P-gp in fetal stomach and in Hp-related gastric carcinogenesis, the epigenetic control of the multi-drug resistance-1 (MDR1) gene, the localization and interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Second, our study reveals a novel in vivo physiological function of ABCB5 in maintaining quiescent LSCs, through ABCB5-dependent regulation of apoptotic signalling pathways. This parallels the known anti-apoptotic function of the ABCB5 homologue ABCB1, shown to be mediated through cross-talk with Bcl-x 14 . Finally, our finding that ABCB5 regulates stem cell maintenance is highly relevant to the study of additional ABCB5-expressing normal stem cell populations in other tissues 6,10 and of slow-cycling ABCB5 + cancer stem cells, in which this role might represent one mechanism of multidrug resistance to cell-cycle-specific agents 10,11,15 .…”
supporting
confidence: 60%
“…Second, our study reveals a novel in vivo physiological function of ABCB5 in maintaining quiescent LSCs, through ABCB5-dependent regulation of apoptotic signalling pathways. This parallels the known anti-apoptotic function of the ABCB5 homologue ABCB1, shown to be mediated through cross-talk with Bcl-x 14 . Finally, our finding that ABCB5 regulates stem cell maintenance is highly relevant to the study of additional ABCB5-expressing normal stem cell populations in other tissues 6,10 and of slow-cycling ABCB5 + cancer stem cells, in which this role might represent one mechanism of multidrug resistance to cell-cycle-specific agents 10,11,15 .…”
supporting
confidence: 60%
“…The levels of GCS mRNA and protein are elevated 4-fold in approximately 80% of metastatic breast cancers, and GCS overexpression is associated with lymph node metastasis in bladder cancers (25,26). In addition, P-gp overexpression is associated with unfavorable prognosis in leukemia, lymphoma, and breast, colon, pancreatic, and gastric cancers (8)(9)(10). The clinical significance of P-gp overexpression has also been studied in HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P-gp regulates cancer proliferation, invasion, and caspase-dependent cell death (6,7). P-gp overexpression in tumors is associated with poor prognosis in several types of cancers (8)(9)(10). The upregulation of rafts and caveolae, including that of the glucosphingolipid-enriched constituents of microdomains, represents another multidrug resistance (MDR) mechanism (11).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that when the tumor cells surface increased expression MDR1 significantly, the accumulation of drugs reduced in cells; when blocked the function of MDR1, the cell resistance would obviously reversed. Moreover, MDR1 could redistribute the intracellular drug, pump the drug out of the cell and reduce intracellular drug accumulation (Hoffmann et al, ; Rocco et al, ).…”
Section: Discussionmentioning
confidence: 99%